2006
DOI: 10.1021/jp0645667
|View full text |Cite
|
Sign up to set email alerts
|

Solvation and Dynamic Behavior of Cyclodextrins in Dimethyl Sulfoxide Solution

Abstract: High-frequency dielectric relaxation behavior up to 20 GHz was investigated for plain (alpha, beta, gamma) and (62 and 100%) methylated cyclodextrins, CDs, in dimethyl sulfoxide, DMSO, solution. Each hydrogen atom of OH groups of the CDs solvated a DMSO molecule for a residence time of 130-180 ps due to the hydrogen bond formation to an oxygen atom of DMSO, and a few DMSO molecules were included in cavities of the CDs for a while similar to the residence time. The overall rotational relaxation modes of solvate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Linear response theory relates the susceptibility tensor χ 0 ( k , ω ) to correlation functions of the Fourier components of the dipole density of the system trueM(truek,t) The two components of trueM(truek,t): trueM(truek,t)=ML(truek,t)+MT(truek,t)can be expressed as follows: ML(truek,t)=j=1Nk^k^·trueμj(t)exp(ik^truerCM(t)) MT(truek,t)=j=1N(1k^k^)·trueμj(t)exp(ik^truerCM(t))where μj(t) is the dipole moment of the j th molecule and rCM(t) the position of its center-of-mass. The components of the susceptibility tensor are given by [1415]: χA0(k,ω)=|…”
Section: Resultsmentioning
confidence: 99%
“…Linear response theory relates the susceptibility tensor χ 0 ( k , ω ) to correlation functions of the Fourier components of the dipole density of the system trueM(truek,t) The two components of trueM(truek,t): trueM(truek,t)=ML(truek,t)+MT(truek,t)can be expressed as follows: ML(truek,t)=j=1Nk^k^·trueμj(t)exp(ik^truerCM(t)) MT(truek,t)=j=1N(1k^k^)·trueμj(t)exp(ik^truerCM(t))where μj(t) is the dipole moment of the j th molecule and rCM(t) the position of its center-of-mass. The components of the susceptibility tensor are given by [1415]: χA0(k,ω)=|…”
Section: Resultsmentioning
confidence: 99%
“…1c ). The intercalation mechanism is evidently less efficient for α-CD, possibly because of its intrinsic lower solubility in the solvent mixture, 30 , 31 and this eventually leads to less soluble CD–PbI 2 complexes. 32 Importantly, the 2.5 M concentrated β-CD based solution exhibits a much higher shear viscosity with respect to the CD-free 1 M solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported on the solvation of CDs by DMSO through hydrogen bonding between the hydrogen atom of the OH moieties in CDs and the oxygen atom of DMSO, 12 which is a prerequisite for the supramolecular chemisorption of CO 2 . 7 However, preliminary NMR experiments on the chemistry of α-CD dissolved in DMSO- d 6 and CO 2 showed no reaction, which indicated the necessity of triggering the nucleophilicity of the α-CD hydroxyl groups using a strong base.…”
Section: Resultsmentioning
confidence: 99%